A 10-Year Bibliographic Analysis of Extracorporeal Membrane Oxygenation (ECMO) Literature - Erenler, Ali Kemal; Öztürk, Ahmet; Gunay, Serkan; Baydin, Ahmet (Bayrakol Medical Publisher, 2023)
Aim: Extracorporeal membrane oxygenation (ECMO) is a life support device providing extracorporeal artificial support to the respiratory system and/or circulatory system for patients who do not benefit from conventional therapies. Material and Methods: A bibliometric search was conducted with information obtained from the Web of Science (WoS) database. Publications on ECMO since 2014 were analyzed. Type of the articles, top authors, language, funding agencies, affiliations, countries, journals were determined. Following statistical analysis of the literature, the top 10 articles on ECMO were investigated in detail. Results: A total of 7940 articles were involved in the study. The majority of the articles were original articles (n=6130, 77.2%). The most productive author was Brodie D (1.9%). English was the most common language. When countries were compared in terms of the number of publications and total citations, the US was the leading country in both categories (n=3103, n=42744, respectively). ASAIO Journal had the highest number of articles (n=491). The analysis of the top 10 most cited articles revealed that the majority of the articles were related to COVID-19. Discussion: Bibliometric studies on a specific subject may shed light on the management of diseases. When the top 10 articles are considered, the use of ECMO in patients with COVID-19 dominates the scientific literature on ECMO.
Erenler, Ali Kemal/0000-0002-2101-8504; Öztürk, Ahmet/0000-0002-9678-2195; Gunay, Serkan/0000-0002-8343-0916;
Keywords: Extracorporeal Membrane Oxygenation; Bibliometrics; Publications